Dynamic vascular optical spectroscopy for monitoring peripheral arterial disease patients undergoing a surgical intervention - Marone, A.; Maheshwari, N.; Kim, S. K.; Bajakian, D. R.; Hielscher, A. H. (Frontiers in Photonics, 2022)
Peripheral arterial disease (PAD) patients experience a reduction in blood supply to the extremities caused by an accumulation of plaque in their arterial system. In advanced stages of PAD, surgical intervention is often required to reopen arteries and restore limb perfusion to avoid necrosis and amputations. To determine the success of an intervention, it is necessary to confirm that reperfusion was achieved after the intervention in areas of the foot that lacked perfusion before the intervention. The standard procedure to obtain this information is to perform repeated X-ray angiography. However, this approach requires a relatively high radiation dose and the extensive use of contrast agents. To overcome these issues, our lab has developed a system that uses dynamic vascular optical spectroscopy (DVOS) to monitor perfusion in the foot in real-time before, during, and after an intervention. In the explorative study presented in this paper, we monitored ten patients undergoing revascularization surgery. We found that there is a clear change in the DVOS signal in cases when reperfusion to affected areas in the foot is established. It was also possible to assess the effects that balloon inflations and deflations and contrast agent injections had on the downstream vasculature of the patients.